1995
DOI: 10.1159/000184313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin on Hydrogen Peroxide Production by Human Polymorphonuclear Leukocytes

Abstract: This study evaluated the effect of insulin on the respiratory burst of human polymorphonuclear leukocytes (PMNLs) and the signalling pathways involved in this process, especially the involvement of protein kinase C (PKC). Isolated human PMNLs from healthy volunteers were incubated with different concentrations of insulin (10-10-10-7 mol/l) and for different durations of incubation (5-90 min). The intracellular production of hydrogen peroxide (H2O2) was detected emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In the different forms of diabetes, insulin levels can be either low (type-1 diabetes) or elevated due to insulin resistance (type-2 diabetes) [18]. The effect of insulin on the in vivo and in vitro functions of neutrophils from diabetics and healthy individuals is still obscure [7,10,11,[19][20][21][22]. Recently, however, it was found that insulin could stimulate chemokinesis in normal human neutrophils [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the different forms of diabetes, insulin levels can be either low (type-1 diabetes) or elevated due to insulin resistance (type-2 diabetes) [18]. The effect of insulin on the in vivo and in vitro functions of neutrophils from diabetics and healthy individuals is still obscure [7,10,11,[19][20][21][22]. Recently, however, it was found that insulin could stimulate chemokinesis in normal human neutrophils [19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Dandona and colleagues (40) proposed that insulin may develop its anti-inflammatory effects via reduction of intranuclear NF-κB and simultaneous stimulation of its inhibitor IκB. Flow cytometry studies of human leukocytes have shown insulin receptors on lymphocytes, monocytes, and neutrophils (41), and insulin has been found to increase the functions of activated lymphocytes (42, 43) and neutrophils (44) and to enhance the proliferation and differentiation of T cells (43). These data suggest that insulin may have some direct effects on certain immune cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Ebenso entscheidend ist die Tatsache, dass eine bessere Stoffwechseleinstellung sogar mit einer geringeren Insulindosis erreicht werden konnte. Dies ist insofern von Bedeutung für den weiteren Krankheitsverlauf eines Patienten, als dass Insulin selbst an der Entwicklung von Komplikationen, besonders der Mikroangiopathieentstehung, mitbeteiligt sein kann [16]. Die gute Stoffwechseleinstellung nach Ablauf von 3 Monaten zeigt den positiven Einfluss der Sanierung des chronischen Entzün-dungsfocus auf den längerfristigen Therapieerfolg bei Diabetikern.…”
Section: Diskussionunclassified